Pengaruh Budaya Organisasi, Kompensasi, Dan Pengembangan Karir Terhadap Talent Retention Dengan Keterlibatan Pegawai Sebagai Variabel Intervening - Aditya Madinta Putra Ginting; Nursaid Nursaid; Abadi Sanosra (Jurnal Manajerial, 2025)
Background – The mutation rate in the Civil Servant environment is still quite high, making it quite difficult to implement talent management. In the 2021 Civil Servant Candidate recruitment, 105 people were recorded as having resigned after being declared to have passed, this resignation was due to a mismatch in salary and placement location. Aims – this study aims to test and determine the direct or indirect influence of organizational culture variables, compensation and career development on talent retention through employee engagement as an intervening variable. Design/Methodology/Approach – This study uses a quantitative research method. Data were collected from 139 respondents who were selected using the random sampling method. The data analysis technique in this study used path analysis using the SEM (Structural Equation Modeling) model or Structural Equation Model with the WarpPLS 7.0 program. Results and Discussion – the results of this study indicate that the variables of organizational culture, compensation and career development partially have a positive and significant effect on talent retention, and also have a positive and significant effect on employee engagement. Based on path analysis, there is a direct and indirect influence of the independent variable on the dependent variable through the intervening variable. Conclusion - employee involvement in Jember district government activities will make employees more loyal and work optimally to achieve the goals of the district government. Improvement of organizational culture, and clarity of career development will increase talent retention, and supported by appropriate compensation. Research implications - based on the results of this study, the Jember district government must foster values ​​and norms in the organization to form a good organizational culture, evaluate and improve the career development system so that employees are more loyal and work optimally. Research limitations - based on the results of the determination coefficient test, the contribution of the independent variables is only 61% and 68%, so it is necessary to add more independent variables so that the results are better. This study has not separated state civil servants from non-state civil servants.